Correlation Between Compensation and Work Satisfaction With Nurses’ Performance Through Motivation in Bethesda Public Hospital of Tomohon - Chyntia Novita Kalalo; Elly Lilianty Sjattar; Rosdiana Natzir (Faculty of Nursing, Universitas Hasanuddin, 2018)
Introduction: Compensation provided by hospital and job satisfaction of nurses can affect the performance of nurses. The research aimed to analyze the correlation between compensation and work satisfaction with nurses’ performance through motivation in inpatient room of Bethesda Publik Hospital of Tomohon. Method: The method used is analytic observational approach with cross sectional study. The number of sample were of 50 respondents. The methods of obtaining the data were questionnaire with Likert scale and observation of nurses’ performance with Guttman scale. The data were analyzed using univariate and bivariate analysis by means of frequency distribution table and cross tabulation with chi square. Results: The research indicate that compensation has a correlation with work load (p=0.003), motivation (p=0.040), and nurses’ performance (p=0.001). Work satisfaction has a correlation with motivation (p=0.002) and nurses’ performance (p=0.000). Motivation has a correlation with nurses’ performance (p=0.013). Conclusion: The management of the hospital should pay attention to compensation given and nurses’ work satisfaction, so the nurses are more motivated to carry out services in a professional nursing care in order that more optimal nurses’ performance.